2018
DOI: 10.1177/0284185118760064
|View full text |Cite
|
Sign up to set email alerts
|

A new imaging technology to reduce the radiation dose during uterine fibroid embolization

Abstract: A substantial 77% reduction of DAP values and 64% and 66% reduction in organ dose on ovaries and uterus, respectively, was demonstrated with the new imaging platform, while maintaining optimal imaging quality and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
3
7
1
Order By: Relevance
“…Therefore, the RAD-IR radiation doses and DRLs should no longer be considered the gold standard for this procedure, considering the changes in x-ray technology. This is supported by similar reductions in patient radiation dose in other recent studies of interventional procedures using new fluoroscopic technology, including uterine fibroid embolization (PKA reduction 77%) (Thomaere et al 2018 ), TACE for hepatocellular carcinoma (PKA reduction 66%) (Schernthaner et al 2015 ), bronchial artery embolization (PKA reduction 59%) (Spink et al 2017 ) and cardiac catherization/angioplasty (PKA reduction 67%) (Buytaert et al 2018 ).…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, the RAD-IR radiation doses and DRLs should no longer be considered the gold standard for this procedure, considering the changes in x-ray technology. This is supported by similar reductions in patient radiation dose in other recent studies of interventional procedures using new fluoroscopic technology, including uterine fibroid embolization (PKA reduction 77%) (Thomaere et al 2018 ), TACE for hepatocellular carcinoma (PKA reduction 66%) (Schernthaner et al 2015 ), bronchial artery embolization (PKA reduction 59%) (Spink et al 2017 ) and cardiac catherization/angioplasty (PKA reduction 67%) (Buytaert et al 2018 ).…”
Section: Discussionsupporting
confidence: 53%
“…21 Despite recording an approximate mean ovarian and uterine dose of 0.04 Gy, these radiosensitive organs are vulnerable to any level of ionising radiation exposure. 21 Therefore, the knowledge and control of dose predictors could reduce the risks of tissue effects and/or stochastic effects to this specific patient population.…”
Section: Discussionmentioning
confidence: 99%
“…20 Since the radiation dose is focused on the pelvis and reproductive organs, Thomaere et al measured the effective organ dose to the ovaries and uterus for fortyone UAE patients. 21 Despite recording an approximate mean ovarian and uterine dose of 0.04 Gy, these radiosensitive organs are vulnerable to any level of ionising radiation exposure. 21 Therefore, the knowledge and control of dose predictors could reduce the risks of tissue effects and/or stochastic effects to this specific patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dose reduction trend overtime may not be seen due to the different interventions used, mixed sample sizes, operator and machine variability, case complexity and the changes in interventional treatment when better quality diagnostic imaging is available with upgraded technology. The future direction of research on radiation exposure and UAE involves the continuation of the studies in comparing dose differentials between older and new angiography x‐ray units that are equipped with real–time image processing techniques and dose reduction algorithms . The current trend in interventional radiology is with the Transradial Approach (TRA), where Resnick et al demonstrated that TRA‐UAE is safe and feasible with patent radial artery at 1‐month follow‐up in all patients.…”
Section: Discussionmentioning
confidence: 99%